2006
DOI: 10.1103/physrevb.73.115435
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic coupling in the icosahedralC602+Jahn-Teller cation: Repercussions of the nonsimple reducibility of theHH

Abstract: Coulomb coupling between the two holes in the fullerene cation C 60 2+ results in high-and low-spin terms.Vibronic coupling of the high-spin terms to a single mode of vibration of h g symmetry can distort the lowest adiabatic potential-energy surface into wells of D 3d , D 5d , D 2h , or C 2h symmetry depending upon the precise nature of the coupling produced by different admixtures of the two sets of coupling coefficients arising from the two H-type irreducible representations appearing in the symmetric part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The expression of the symmetrized h g displacements has been presented in Refs. [39,61,73]. The following symmetrized displacements contain those by g g modes as well as the h g displacements.…”
Section: Evaluation Of the Effect Of The Quadratic Coupling On The Lomentioning
confidence: 99%
“…The expression of the symmetrized h g displacements has been presented in Refs. [39,61,73]. The following symmetrized displacements contain those by g g modes as well as the h g displacements.…”
Section: Evaluation Of the Effect Of The Quadratic Coupling On The Lomentioning
confidence: 99%
“…This is the usual approach for combining interelectron and JT interactions, 1,2 which has been used in a number of previous works. 1,2,[15][16][17][18][19][20]24 Starting from this basis, Hamiltonians can be constructed that incorporate the interelectron interactions by placing different terms at different energies. Additional contributions to the Hamiltonian are then added to incorporate JT interactions within the terms and between coupled terms.…”
Section: A Hamiltonians For P N ⊗ H Systemsmentioning
confidence: 99%
“…Furthermore, applying operations of the icosahedral group to the Q γ (γ ∈ {θ, , 4,5,6}) shows that at least one minimum of each of D 5d , D 3d , D 2h , and C 2h can be found that involves just Q θ , Q , and Q 6 , so we can set Q 4 = Q 5 = 0. 18 Further conditions to generate minima of a given symmetry are given in Table I. 18 Using these conditions greatly simplifies the problem of finding JT minima, as instead of minimizing the energy with respect to the five Q γ , it is only necessary to carry out a minimization in one dimension (for D 5d / D 3d symmetry), two dimensions (for D 2h symmetry), or three dimensions (for C 2h ).…”
Section: Symmetry Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this complication can be dealt with (see e.g. [48]), it is often easier to work in terms of a single, effective mode as this is far simpler and reproduces most of the important aspects of the problem. In fact, in the current context, even the details of some effective mode of vibration are effectively irrelevant as we are ignoring the distortion of the C 60 cage.…”
Section: A Review Of Jahn-teller Effects In Discrete Fullerene Systemsmentioning
confidence: 99%